Increased cancer risk in HIV-infected individuals occupationally exposed to chemicals: Depression of p53 as the key driver. - Donald C Udah; Adeleye S Bakarey; Gloria O Anetor; Maxwell Omabe; Victory F Edem; Olusegun G Ademowo; John I Anetor (Public Library of Science (PLoS), 2024)
The growing exposure to occupational chemicals and the spread of human immunodeficiency virus (HIV) infection are major global health issues. However, there is little data on the carcinogenic risk profile of HIV-infected individuals who have been occupationally exposed to chemical mixtures. This study therefore investigated the levels of cancer risk biomarkers in HIV-infected individuals exposed to occupational chemicals, exploring the relationship between apoptotic regulatory and oxidative response markers as a measure of cancer risk. Study participants (mean age 38.35±0.72 years) were divided into four groups according to their HIV status and occupational chemical exposure: 62 HIV-positive exposed (HPE), 66 HIV-positive unexposed (HPU), 60 HIV-negative exposed (HNE), and 60 HIV-negative unexposed (HNU). Serum p53, β-cell lymphoma-2 (bcl2), 8-hydroxydeoxyguanosine (8-OHdG), superoxide dismutase (SOD), and malondialdehyde (MDA) were measured using standard methods. Clusters of differentiation 4 (CD4+) T-lymphocytes were enumerated using flow cytometry. Serum p53 and bcl2 levels in HPE (0.91±0.11ng/ml and 122.37±15.77ng/ml) were significantly lower than HNU (1.49±0.15ng/ml and 225.52±33.67ng/ml) (p < 0.05), respectively. Wildtype p53 and bcl2 were positively and significantly correlated with 8-OHdG (r = 0.35, p<0.001; r = 0.36, p<0.001) and SOD (r = 0.38, p<0.001; r = 0.39, p<0.001). After controlling for gender, age, BMI, and cigarette smoking, both HIV status and SOD activity were significantly associated with wildtype p53 and bcl2 (p < 0.05). Malondialdehyde was significantly higher in the HPE (0.72 ± 0.01 mg/ml) than in the HNE (0.68 ± 0.01 mg/ml) and HNU (0.67 ± 0.01 mg/ml) groups (p < 0.05). The HPE group showed significantly lower CD4 counts than the HNE and HNU groups. Individuals who are HIV-infected and occupationally exposed to chemicals have a constellation of depressed immunity, elevated oxidative stress, and loss of tumour suppressive functions, which together intensify cancer risk, providing valuable scientific and public health bases for preventive measures in this vulnerable population.